May you live in interesting times - Glück, Tereze, 1945- (Iowa short fiction award., 1995)
Twenty-one stories, mostly on women. In the title story a woman reminisces about her loves, Gone Fishing is on a romance by e-mail, while Bill Hilgendorf is a woman's reflections on her childhood sweetheart. A debut in fiction.